Correlation between rheumatoid arthritis and periodontitis - Zielińska, Anna; Tabarkiewicz, Jacek (European Journal of Clinical and Experimental Medicine, 2022)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. The association between periodontitis (PD) and rheumatoid arthritis (RA) has been analyzed and described in literature. Periodontal pathogens, such as Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans are pointed as the common factors for both diseases. In this work we demonstrate that treatment of dental and oral diseases is an unconditional requirement for patients with RA. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. PubMed was searched with the keyword “rheumatoid arthritis” and “periodontitis” from May 1999 to January 2022, showed 181 articles. Ultimately 72 articles were included in the review. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Analysis of the literature. The above mentioned pathogens exhibit multiple mechanisms that disturb immune and inflammatory responses of the human organism. Those mechanisms lead to the periodontal disease (PD) that may activate the systematic reactions which in turn lead to intensification of systematic diseases such as rheumatoid arthritis (RA). P. gingivalis has the ability to expresses PAD enzyme (peptidylarginine deiminase) and activates the citrullization process. Moreover, the bacterium produces gingipain cysteine proteinases, which degrade the mechanisms of immunological system. The latter pathogen, A. actinomycetemcomitans, expresses hypercitrullization in neutrophils. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Both pathogens influence inflammatory response of the organism, through the common pro-inflammatory mediators for periodontitis and rheumatoid arthritis, intensify the clinical manifestations of both diseases.